Efforts to Improve Teacher Competence in Preparation of Question Items through a Workshop on Self Development in Montong Gading 1 High School - Fathan, Fathan (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
Student learning outcomes articulate what students must know or can do after completing learning. A good test instrument can help teachers improve learning and provide accurate information to students who have not or have achieved competency based on goals. This study aims to see to what extent the implementation of self-development workshops can improve teacher competency in the preparation of items at SMAN 1 Montong Gading. This study is action research on the subject of all 24 subject teachers. The teacher is divided into groups with the same learning eyes. The self-development workshop was carried out in 2 cycles with each stage namely the planning stage, the implementation phase, the observation stage, and the reflection stage. The results of the study showed an increase in each cycle if reviewed from before the implementation of the self-development workshop in all aspects. This point shows that the ability of teachers to compile items before the workshop is still in the less category in the aspect of conformity with learning objectives, only 16.7%, experiencing an increase in the first cycle to 33.3%, in the second cycle to 58.3%. In the aspect of conformity with aspects of behavior there is an increase from before the workshop was held with a percentage of 20.8% to 75% in the cycle, while in the aspect of use that also experienced an increase from before the workshop was held in the amount of 45.8% to 79.1% in the cycle II.